Más allá de Menem (o de la conflictiva y nunca acabada reforma del Estado en la Argentina democrática) - Camou, Antonio Adolfo Marcial (1999)
This article proposes three objectives. The first one, starts from a schematic presentation of political periods in the historical development of the State in Argentina, offering a tight summary of conflictive functioning and the “perverse” relationship between the State and the market starting from the second post-war. Secondly it analyzes the link between variables of political institutions and economic reforms, trying to place the political and economic changes held in Argentina during recent years within the frame of comparative academic literature on the structural adjustment in Latin America. Finally, having as a central point the argument that the political and institutional factors that made possible the rapid change in the economic orientation during the Menem Administration (particularly the concentration of political power not subject to an effective control of Congress and the inorganic leadership of Menem), have left a trail of problems that hinder facing with an advantage the complex phase of the reconstruction of the productive profile of the country and the no less complex challenge of the “second generation” of State reforms.